Negotiating Early Job Insecurity: Well-being, Scarring and Resilience of European Youth - Christer Hyggen (Edward Elgar Publishing, 2019)
Offering new knowledge and insights into European job markets, this book explores how young men and women experience job insecurity. By combining analysis of original data collected through a variety of innovative methods, it compares the trajectories of early job insecurity in nine European countries. Focusing on the ways in which young adults deal with this by actively increasing their chances of getting a job through a variety of methods, as the book shows how governmental policies can be altered to reduce early job insecurity.